Improving Self Regulated Learning Through Cooperative Learning Jigsaw Type - Arjanggi, Rusena; Setiowati, Erni Agustina (UI Scholars Hub, 2013)
The main purpose of this study was to examine effectiveness of cooperative learning type jigsaw to enhance self regulated learning. Experiment design is used by implementing jigsaw classroom for improving self regulated learning. Data were collected by self regulated learning scale adapted from MSLQ (developed by Pintrich et al., 1991) to know the student’s profile of active learning. As known, the changes of paradigm in instruction from teacher or lecture center to student active learning have many problems. One of the causes of this condition is most of lecture still use traditional models of instruction that led lecture more active than students. Sixtyseven student from diploma degree in nurse faculty of Sultan Agung Islamic University involved in this study. Then, subject divided equally into two groups, 33 student for control group and 34 student for experiment group. The result showed that cooperative learning type jigsaw has significantly effect to self regulated learning. Jigsaw learning can improve student motivation significantly, however, the effect on the regulation of learning strategies was not found.